A város és az ifjúság – Budapest, Győr és Szarvas a fiatalok szemével - Egedy, Tamás (Tér és Társadalom, 1996)
We can clearly see from the results of the study how different and still similar are the opinions of the young about towns and cities, their present and future. They are different, since neither in Hungary nor in the whole world can we fmd two towns that are absolutely identical in structure, the thinking and opinions of their population. At the same time they are similar, as it is about the representatives of the same generation who, deriving from their age, have a similar way of thinking, perceive and experience the world surrounding them in a similar way and their value system does not vary much, either. Evaluating the responses at local levei, differences were more striking, whereas looking at the opinions about towns and cities at the global levet, similarities could clearly be observed.